Faktor – Faktor Yang Mempengaruhi Keputusan Pembelian Pasta Gigi Formula Pada Desa Denai Kuala Pantai Labu Deli Serdang - rukmini rukmini; Muhammad Rizaldy Wibowo; Sri Murniyanti (CERED Indonesia Institute, 2021)
This study aims to determine the factors that influence the decision to purchase Formula Toothpaste in the village of Denai Kuala Pantai Labu Deli Serdang. Some of the proxied factors include advertising and price on the decision to purchase Formula Toothpaste at Desa Denai Kuala Pantai Labu Deli Serdang. It aims to analyze the effect of advertising and price on purchasing decisions of formula toothpaste in the community of Denai Kuala Village, Pantai Labu District, Deli Serdang. This study uses quantitative data analysis with the population being the people of Denai Kuala Village, Pantai Labu Deli Serdang District. Sampling using the Slovin formula with an error rate of 10% so that the research sample was obtained as many as 97 people. The data analysis method used multiple linear regression, t test (partial), F test, and coefficient of determination test using SPSS version 22.00 for windows. The results of the multiple linear regression test obtained the equation Y = 28.84 - 0.802X1 + 0.331X2 . This value indicates that the two independent variables make a significant contribution in determining the Y variable.